Pengaruh Penyuluhan Gizi Terhadap Pemahaman Ibu Hamil Dalam Mendukung Kesehatan Ibu dan Janin - Rachman, Arif; Arfiyanti, Arfiyanti; Krista, Alfa januar; Soeroso, Venty Muliana Sari; Ilmi, Abdul Aziz Maulana (Ilin Institute, 2025)
Nutritional status and weight of pregnant women affect fetal growth. The nutritional quality of pregnant women's food determines the nutritional adequacy needed for the health of the mother and fetus. The nutritional status of pregnant women, in addition to ensuring optimal fetal growth and development, also supports the delivery process, breast milk nutrient reserves, and the physical and intellectual development of the baby in early life. The purpose of this counseling is to increase the understanding of pregnant women in consuming food for the health of the mother and fetus. The method used in this study is a survey by filling out pre-test and post-test questionnaires. As many as 82% of pregnant women are of reproductive age. History of miscarriage in 24% of pregnant women. Education level, D4/S1 graduates (35%), high school graduates (35%), D3 graduates (24%), and S2 graduates (6%). Pregnant women who participated in counseling were pregnant with their first child (65%), followed by their second child (29%) and third child (6%). There was a significant increase in the knowledge of pregnant women, the results of the pre-test were 66% and the post-test reached 100%.